(3bQI Yjf GdbQGA aj GdbQGAGJs - (3CHh ESMGb EHQGgje Hf eMeO Hf Ydj GdbhGSj GdeQfOjs
(3ChdgG (B:s
(3CeG HYO , aEfi LeYJ gPG GdcJGH dCLd CHfi hbQI Yjfi hKeQI aDGOi , djYde aGFOI RGFOI Ydi GdbQGAGJ GdSHY , hjaJNQ Hg Ydi Gdcd hGdLeY , hjOYh CHjg s
(3BNQgG (B:s
(3ShQI Gdadb (B: (3eG Ndb HQaY GdNGA hcSQ GddGe Je GdbQGAGJ hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3Ydi GdhQbI GdChdi CfgG HNW GdeUfa hYdjgG eWGdYI bGe HgG eMeO Hf Ydi Hf GHQGgje GdTGaYi GdHYdi SfI (B747 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B224s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdbQGAGJ hGdJLhjOs